2018
DOI: 10.2519/jospt.2018.7923
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Osteonecrosis of the Knee

Abstract: A 69-year-old man was referred to physical therapy by his primary care physician for an insidious onset of right medial knee pain that had been present for over 4 weeks. Due to the disproportionate response following initial management, he was referred to an orthopaedist for imaging. Magnetic resonance imaging revealed medial femoral condyle osteopenia, bone marrow edema, and subchondral bone collapse, and subsequently the patient was diagnosed with spontaneous osteonecrosis of the knee. J Orthop Sports Phys … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 0 publications
0
15
0
4
Order By: Relevance
“…In this regard, Geijer et al [29] reported the course of a lesion the healing of which took over 2.5 years. By contrast, clinical symptoms often improved signi cantly after 2 to 6 weeks [13,21,22,25,29,30,33]. A complete disappearance of symptoms was described at the earliest after 2 to 3 months of continuous therapy [7,13,17].…”
Section: Therapy Outcomesmentioning
confidence: 98%
See 4 more Smart Citations
“…In this regard, Geijer et al [29] reported the course of a lesion the healing of which took over 2.5 years. By contrast, clinical symptoms often improved signi cantly after 2 to 6 weeks [13,21,22,25,29,30,33]. A complete disappearance of symptoms was described at the earliest after 2 to 3 months of continuous therapy [7,13,17].…”
Section: Therapy Outcomesmentioning
confidence: 98%
“…The MRI-based criteria used for the differential diagnosis of SONK were found to be heterogeneous. While some authors screened images for speci c features, such as focal hypointense areas on T1-or T2-weighted images, visible fracture lines or focal epiphyseal contour depressions [7,[13][14][15][16][17][18][19][20][21][22][23][24], others diagnosed SONK in the presence of bone marrow edema (BME) accompanying typical symptoms [25][26][27]. Two case reports radiologically demonstrated the primary overlay of fracture lines by BME [28,29].…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
See 3 more Smart Citations